2015
DOI: 10.1177/0899764015581055
|View full text |Cite
|
Sign up to set email alerts
|

High-Stakes Volunteer Commitment

Abstract: This study examines the social network ties, motivations, and experiences of highstakes volunteers (HSVs): individuals who fulfill long-term, consistent, and intense time commitments providing medical, social, and/or psychological assistance. Interview, focus group, and observational data from three settings (volunteer firefighting, victims' services/advocacy, outreach for at-risk youth) were analyzed using qualitative methods. Accordingly, five types of HSVs (stable lifer, imbalanced lifer, conventionalist, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 36 publications
4
18
0
Order By: Relevance
“…For example, a fire department captain who distributes responsibilities according to firefighters' individual strengths and desires raises the engagement of volunteers. The family‐like structure often present in volunteer fire departments can also emphasize the beneficial role of such relational leadership (Haski‐Leventhal and McLeigh ; McNamee and Peterson ). Second, considering that volunteer firefighters are more interested in making a real contribution to society (Thompson and Bono ), they are comparatively prone to be affected by the inspirational aspect of transformational leadership behavior (Rowold et al ; Wright et al ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a fire department captain who distributes responsibilities according to firefighters' individual strengths and desires raises the engagement of volunteers. The family‐like structure often present in volunteer fire departments can also emphasize the beneficial role of such relational leadership (Haski‐Leventhal and McLeigh ; McNamee and Peterson ). Second, considering that volunteer firefighters are more interested in making a real contribution to society (Thompson and Bono ), they are comparatively prone to be affected by the inspirational aspect of transformational leadership behavior (Rowold et al ; Wright et al ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…In a volunteer context, transformational leadership is particularly vital because such organizations naturally pursue strong service‐oriented missions (Wright, Moynihan, and Pandey ) and seek to deploy volunteers who generally strive to identify with their values and goals (Hustinx and Handy ). This is particularly true for volunteer organizations that pursue high‐risk activities (for example, firefighting), which require extensive training and teamwork of volunteers (McNamee and Peterson ).…”
mentioning
confidence: 99%
“…Volunteerism is an important focus for future research on emotional labour in NGOs. Although unpaid, it is difficult to argue that 'HSVs' [McNamee and Peterson, (2016), p.276] either do not work, or that their emotional labour is actually emotion work. Yet, emotional labour theory has not yet begun to explain what volunteers and NGOs exchange in lieu of wages.…”
Section: Conclusion: Limitations and Future Researchmentioning
confidence: 99%
“…Contributions to the volunteer motivation literature offer some guidance here, particularly those tackling how 'crisis' volunteers respond to and are affected by high-risk situations, including mental health crisis centres, armed conflicts, refugee centres and epidemics. [21][22][23][24][25][26] Anthropological investigations of volunteers in health emergencies are relatively rare, but can illuminate how they make sense of the pandemic, their work and the socio-political settings and organisation hierarchies within which they operate. 27 One study demonstrated the importance of exploring motivation through an anthropological lens, showing how changing socio-political contexts influenced volunteer engagement during Germany's immigration crisis.…”
Section: Introductionmentioning
confidence: 99%